Plasmacytoid Dendritic Cells Provide Protection Against Bacterial-Induced Colitis - Rahman, Tania; Brown, Andrew S.; Hartland, Elizabeth L.; van Driel, Ian R.; Fung, Ka Yee (Frontiers in Immunology, 2019)
We have examined the influence of depleting plasmacytoid dendritic cells (pDC) in mice on the immune response to the gut pathogen Citrobacter rodentium, an organism that is a model for human attaching effacing pathogens such as enterohaemorraghic E. coli. A significantly higher number of C. rodentium were found in mice depleted of pDC from 7 days after infection and pDC depleted mice showed increased gut pathology and higher levels of inflammatory cytokines in the colon upon infection. pDC-depletion led to compromising of the gut mucosal barrier that may have contributed to increased numbers of C. rodentium in systemic organs. pDC-depleted mice infected with C. rodentium suffered substantial weight loss necessitating euthanasia. A number of observations suggested that this was not simply the result of dysregulation of immunity in the colon as pDC-depleted mice infected intravenously with C. rodentium also exhibited exacerbated weight loss, arguing that pDC influence systemic immune responses. Overall, these data indicate that pDC contribute at multiple levels to immunity to C rodentium including control of bacterial numbers in the colon, maintenance of colon barrier function and regulation of immune responses to disseminated bacteria.